Islamic Economic Ethical Values and The Urgency of Work Ethic in Improving The Welfare of The Puger Kulon Coastal Community Jember - Fauzia, Ika Yunia; Ramadhani, Kurniawan (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
While coastal communities are often associated with wasteful lifestyles that rely solely on the sea, in Puger Kulon, coastal communities also prioritize a strong work ethic and adhere to Islamic economic principles in order to achieve prosperity in their daily lives. The purpose of this study is to present an overview and justification of the application of Islamic economic ethical norms and the necessity of work ethics in order to enhance the well-being of the coastal community of Puger Kulon. This research used a qualitative, live history/phenomenological research methodology, with the research subject utilizing a snowball as the research tool. The researcher examined data from multiple sources, with Mr. Slamet, Mr. Doni, Mr. Rozak, and Habib Isa Mahdi serving as the primary sources. This study's goal was to better understand Islamic economics' ethical principles and the critical role that work ethics play in enhancing the wellbeing of Puger Village's coastal inhabitants. Several findings from this study included the fact that fisherman received assistance from their wives in order to work during the off-season.